2020
DOI: 10.1007/s00270-020-02549-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Tumor Progression After Percutaneous Ablation of Hepatocellular Carcinoma: Comparison Between Monopolar Radiofrequency and Microwaves. Results of a Propensity Score Matching Analysis

Abstract: Je remercie le Pr Vilgrain d'avoir accepté de présider ce travail de thèse. Votre bienveillance et vos conseils m'auront permis de m'élever. Je vous remercie d'avoir créé et d'entretenir dans votre service cette ambiance unique, donnant l'envie et le courage de faire, et de bien le faire. Je remercie le Pr de Kerviler d'avoir accepté de juger ce travail de thèse. Je vous remercie de me faire confiance et de me donner l'opportunité de travailler à vos côtés. Cela fait bien trop longtemps que j'attends. Je remer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Potretzke et al found a 2-fold increased risk of long-term progression after RFA with respect to MWA: HCC greater than 3 cm in diameter showed the greatest difference in progression risk between MWA and RFA [ 14 ]. A recent study published by Bouda et al found a higher efficacy of MWA compared to RFA ablation in 149 patients with naive HCC at very early or early stage in terms of local tumor progression, but they did not evaluate overall survival [ 15 ]. On the other hand, the study of McDevitt et al showed no difference in the risk of primary failure or local progression between RFA and MWA in 136 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Potretzke et al found a 2-fold increased risk of long-term progression after RFA with respect to MWA: HCC greater than 3 cm in diameter showed the greatest difference in progression risk between MWA and RFA [ 14 ]. A recent study published by Bouda et al found a higher efficacy of MWA compared to RFA ablation in 149 patients with naive HCC at very early or early stage in terms of local tumor progression, but they did not evaluate overall survival [ 15 ]. On the other hand, the study of McDevitt et al showed no difference in the risk of primary failure or local progression between RFA and MWA in 136 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous minimally-invasive locoregional treatment of HCC includes transarterial chemoembolization (TACE), transarterial radioembolization (TARE), radiofrequency (RFA), or microwave (MWA) ablation (thermal ablation), as well as cryoablation [ 194 , 195 , 196 , 197 , 198 , 199 , 200 ]. Among these, thermal ablation and TACE are the most widely adopted [ 200 ].…”
Section: Imaging Assessment Of Hcc Following Percutaneous Locoregiona...mentioning
confidence: 99%
“…The authors concluded that the percentage of local tumor progression (LTP) was lower after MW in comparison to RF independently from tumor dimension and the vicinity to vascular structures, and RF ablation was identified as an independent predictor for LTP, even in lesions up to 30 mm. [ 29 ].…”
Section: Discussionmentioning
confidence: 99%